Effect of Class-Wide Peer Tutoring on Students’ Performance in Physics in Dekina, Nigeria - Abdulrasaq Oladimeji Akanbi (Universitas Majalengka, 2022)
The study investigated the effect of Class-wide Peer Tutoring (CWPT) on students’ performance in physics in Dekina, Nigeria. Two co-education public secondary schools were purposively selected. A total of 64 (male = 31, female = 33) senior school two (SSII) students were randomly selected from the sampled school. A quasi-experimental design was adopted for the study. The instrument used for this research was a 20-multiple-choice projective Motion Test (PMT) developed by the researcher. The treatment in the experimental group was the teaching of Projectile Motion using the CWPT strategy. Mean, standard deviation, and ANCOVA was used to analyze the data collected. The findings revealed that there was a significant difference between the performance of the experimental group and the control group in the favour of the experimental group and no significant difference in the performance of male and female students when both are taught Projectile Motion using CWPT. It is recommended among others that teachers should be trained to adopt classwide peer-tutoring in schools since it facilitates the academic performance of students in physics.